PENINGKATAN KAPASITAS LEMBAGA DESA MELALUI PELATIHAN PELAPORAN BERBASIS MICROSOFT OFFICE DI DESA CEWENG KABUPATEN JOMBANG - Erlangga, Hans Candra; Prasetyo, Gunawan Heri; Yasin, Mohamad Zulkifli; Fadhilah, Ayu Nur; Bachruddin, Bachruddin (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
Capacity building aims to enhance the capabilities of village institutions in Ceweng Village, Jombang Regency, through reporting training based on Microsoft Office. This training is designed to strengthen the administrative and reporting skills of village institutions, which are essential elements in supporting transparency and accountability in village governance. The method applied in this study is a participatory approach by conducting a series of workshops and intensive training sessions. The training materials include an introduction to Microsoft Office basics, data processing using Excel, and report creation with Word. The study results show a significant improvement in the ability of village institutions to use Microsoft Office to compile more systematic and professional reports. Additionally, this training also enhances the understanding of village institutions on the importance of accurate and effective reporting in supporting data-based decision-making. Thus, this training is expected to serve as a model for capacity-building programs for village institutions, particularly in Jombang Regency